ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ УСТАНОВОК ТЕРМІЧНОГО ЗНЕШКОДЖЕННЯ ПОБУТОВИХ ВІДХОДІВ ШЛЯХОМ УТИЛІЗАЦІЇ СКИДНОЇ ТЕПЛОТИ - Fialko, N.M.; Navrodska, R.; Shevchuk, S.; Gnedash, G. (Institute of Engineering Thermophysics of NAS of Ukraine, 2024)
The work is devoted to research on the creation of recovery exchanger for waste heat exhaust gases of household waste incineration plants. The purpose of the work is to develop a technical solution for the heat recovery exchanger of waste incineration plants (WIP) and determine its thermal efficiency indicators. The main objectives of the study were to analysis of the modern experience of using the WIP and establish requirements for the creation of the exhaust gas heat recovery exchanger, develop a new technical solution for the heat recovery exchanger, and determine the change patterns in its main thermal indicators in different operating modes of the WIP. The known methods of thermal calculation of heat exchangers and the results of previous studies on the development and implementation of heat recovery equipment operating on dusty gases were used. The results of work on the creation of a new technical solution for an air-heating heat recovery exchanger with the ability to clean working surfaces from dust deposits are presented. The heat exchange surface of the heat recovery exchanger is composed of steel panels formed by tubes with membranes. The tubes applied have circular flow turbulizators on their internal surfaces. Turbulizators provide heat transfer intensification by 1.4 to 1.8 times with a moderate increase in aerodynamic resistance compared to other methods of heat transfer intensification. The regularities of changes in the main indicators of the heat recovery unit in different operating modes during the year in the practical range of changes in its input parameters were established. The research results show that, depending on the initial temperatures of gases and air, the excess air ratio in exhaust gases and the dust level of the working surface, the heat recovery exchanger provides heating capacity of 72-263 kW; cooling of exhaust gases to a temperature of 107-245 °C; heating of air to 96-220 °C. It was also established that the deposition of dust on the heat exchange surface of the heat recovery unit under the considered conditions leads to a decrease in the heating air temperature by 1.3-1.4 times and an increase in the final exhaust gas temperature by 1.1-1.2 times. At the same time, the heating capacity of the heat recovery exchanger is reduced by half. To increase heat recovery efficiency, it is necessary to periodically clean the working surfaces of the heat recovery unit with compressed air.